Saliva as a Diagnostic Tool in Forensic Odontology: Scope and Methods - Chinnamurthy , Bhargavi; Jyothirmai , Koneru; Reddy , Reddy Sudhakara; Ramesh , Tatapudi; Babu , B. Ananda; Darna , Geetanjali (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Human body fluids such as blood and saliva are the most common sources of biological trace material found at a crime scene. Over the last decade or so there has been a growing interest in saliva and its use as a tool in forensic odontology as an alternative to blood or urine. The added advantage of its noninvasive method of collection even by individuals with limited training, makes saliva a popular fluid for forensic analysis. Saliva is mainly looked for in cases of drug abuse, sexual assault, and in cases involving animal or human bites. This oral fluid has an immense role in linking of suspects or victims to a crime scene, as well as in establishing the identity of unknown individuals. This review details about the various application of saliva in the field of forensic odontology such as age, gender and blood group determination, drug, cigarette consumption detection to the storage of saliva samples for future references.